Vulnerability assessment of coastal fisher households in Kerala: A climate change perspective - Salim, Shyam S; Zachariah, P. U.; Kripa, V.; Mohan, Anjana; Ambrose, T. V.; Manju Rani, S. (Indian Journal of Fisheries, 2014)
Climate change, a global challenge facing mankind necessitates governments to develop mitigation and adaptation plans. The climate change has multidimensional impacts on environment, fishery, social, economic and development drivers. The perception level of the primary stakeholders leads to their proactive participation in disaster management plans. The present paper assessed the vulnerability of 318 fisher households in Alappuzha District of Kerala using PARS (parameter, attribute, resilient indicator and score) methodology. The methodology provides prioritisation and ranking of the different impacts as perceived by the fishers on environment, fishery and socio-economic parameters. The vulnerability indices were worked out for the fisher households. The fisher’s perception revealed that fishery was most impacted followed by economic and environmental impacts. Social impact was the least as opined by fishers. The study indicates that long term effects of climate change aren’t realised/perceived/impacted much among the fisher households. The fishers were more prone to loss in fishing days due to erratic monsoon. The results suggest immediate need to improve the primary stakeholders awareness by involving them in disaster preparedness, management and mitigation planning as well as implementation process.